Lipid Composition of Outer Leaflet of Chloroplast Outer Envelope Determines Topology of OEP7 - Schleiff, Enrico (The American Society for Cell Biology, 2001)
OEP7, a 6.7-kDa outer envelope protein of spinach chloroplasts inserts into the outer envelope of the organelle independent of a classical cleavable targeting signal. The insertion of OEP7 was studied to describe the determinants for association with, integration into, and orientation of the protein in the outer envelope of chloroplasts. The insertion of OEP7 into the membrane is independent of outer membrane channel proteins and can be reconstituted with the use of protein-free liposomes. In situ, the binding of OEP7 to the membrane surface is not driven by electrostatic interaction because reduction of phosphatidylglycerol or phosphatidylinositol did not reduce the association with the liposomes. The positively charged amino acids flanking the transmembrane domain at the C terminus are essential to retain the native N(in)-C(out) orientation during insertion into chloroplasts. OEP7 inserts with reversed orientation into liposomes containing the average lipid composition of the outer envelopes. The native like N(in)-C(out) orientation is achieved by reduction of the phoshpatidylglycerol concentration mimicking the composition of the outer leaflet of the outer envelope of chloroplasts. We conclude that the unique lipid composition of the outer leaflet due to lipid asymmetry of the outer envelope is essential for the correct topology of OEP7.